ADAPTATION OF UKRAINIAN HEALTH CARE LEGISLATION TO EUROPEAN STANDARDS - Rohova O.G. (Pressing Problems of Public Administration, 2018)
The actual state of adaptation of Ukrainian Health Care legislation to the proper European standards is analyzed in the article. Achievement and problems of adaptation of legal acts of Ukraine is considered in relation to a manufacturing and distribution of medications, grant of medical services, to the requirements of European medical practice. Major tasks of the legal providing adaptation of Health Care to methodological approaches of the acquis communautaire are determined.